2010
DOI: 10.1093/toxsci/kfq239
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profile Indicative of Immunotoxic Exposure: In Vitro Studies in Peripheral Blood Mononuclear Cells

Abstract: Investigating the immunotoxic effects of exposure to chemicals usually comprises evaluation of weight and histopathology of lymphoid tissues, various lymphocyte parameters in the circulation, and immune function. Immunotoxicity assessment is time consuming in humans or requires a high number of animals, making it expensive. Furthermore, reducing the use of animals in research is an important ethical and political issue. Immunotoxicogenomics represents a novel approach to investigate immunotoxicity able of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Hochstenbach et al (2010) have recently reported a set of 48 genes that can be used to distinguish immunotoxic from non-immunotoxic compounds using human peripheral blood mononuclear cells. these genes might be considered candidate biomarker genes for immunotoxicity screening.…”
Section: Tab 3: Major Limitations and Future Research Needs In In VImentioning
confidence: 99%
“…Hochstenbach et al (2010) have recently reported a set of 48 genes that can be used to distinguish immunotoxic from non-immunotoxic compounds using human peripheral blood mononuclear cells. these genes might be considered candidate biomarker genes for immunotoxicity screening.…”
Section: Tab 3: Major Limitations and Future Research Needs In In VImentioning
confidence: 99%
“…To distinguish immunotoxic from non-immunotoxic compounds, human peripheral blood mononuclear cells should be preferably used. Identification of the gene signature of direct immunotoxicants should include testing the effects of large number of compounds on the transcriptome of human cells such as Jurkat T-cells (Hochstenbach et al, 2010). Diverse modes of action are involved in direct immunotoxicity and a set of pathways or genes, rather than one single gene, should be used to screen compounds for immunotoxicity and genotoxicity (Hartung and Corsini, 2013;Shao et al, 2013).…”
Section: Future Perspectivementioning
confidence: 99%
“…The following studies were identified on acrylamide, including eight rat based studies (Barber and LoPachin, 2004;Barber et al, 2007;Cha et al, 2009;El-Sayyad et al, 2011;Feng et al, 2011;Hasegawa e al, 2008;Hochstenbach et al, 2010;Lampen et al, 2009;Mei et al, 2008;Oshida et al, 2011;Schwend et al, 2009;Seale et al, 2012;Sun et al, 2010;Zhang et al, 2011c;Wang Z et al, 2010). Four cell based studies involve a variety of human cell types.…”
Section: Hazardmentioning
confidence: 99%